The Mythology of Dreams in Al-Damiri’s Book The Great Life of Animals and Its Impact on Islamic Collective Consciousness in the Era of the Mamluk Sultanate (784–923 AH) - Salam Nasser Wali AL-Adami, Dr. (lark, 2026)
This study examines the mythology of dreams as described in the Great Book of Animal Life by the historian Al-Damiri (d. 808 AH) and its impact on Islamic collective consciousness in the Mamluk era, particularly during the era of the Circassian Mamluks (784-923 AH). These dreams, which took the form of animals, reflected a symbolic image; as they were not merely fleeting individual experiences, but rather conveyed to us an effective symbolic mythological system that played a direct role in producing social meanings and guiding moral behaviour and general traditions, as well as legitimising authority. The study was distinguished by its presentation of two images from animal mythology. The first was the mythology of predatory animal dreams, which evoked the image of the lion, the tiger and the wolf as reflections of coercive authority and representations of the enemy and political danger, revealing people’s fears of violence and political and military conflict. The second image came under the title of the mythology of economic and service animals, from which horses, camels, cows, and sheep were chosen because of their direct connection to the flock, money, taxation, and work, and their embodiment of the social and behavioural structure of the Mamluk era. The study concluded that animals and their dream images in Al-Damiri’s codex were not treated as mere natural beings, but rather as symbolic and mythological mediators that reflected the beliefs and perceptions of society and authority, along with the accompanying meanings of strength, weakness, fertility, and crises. Dreams intersected between the religious and the political and, through this symbolism, became a tool for reshaping collective consciousness after a period of multiple transformations and crises in various fields. The study relied on several scientific approaches that combined historical analysis of texts, mythological interpretation of animal dreams, and a close examination of dreams as a reflection of the nature of society and the mind.